Entrepreneurship and Role Models - Niels Bosma; Jolanda Hessels; Veronique Schutjens; Mirjam van Praag; Ingrid Verheul (Tinbergen Institute, 2011)
In the media role models are increasingly being acknowledged as an influential factor in explaining the reasons for the choice of occupation and career. Various conceptual studies have proposed links between role models and entrepreneurial intentions. However, empirical research aimed at establishing the importance of role models for (nascent) entrepreneurs is scarce. Knowledge of the presence of entrepreneurial role models, their specific functions and characteristics is therefore limited. Our explorative empirical study is a first step towards filling this gap. Our study is based on the outcomes of a questionnaire completed by a representative sample of 292 entrepreneurs in three major Dutch cities - entrepreneurs who have recently started up a business in the retail, hotel and restaurant sectors, business services and other services. We provide indications of the presence and importance of entrepreneurial role models, the function of these role models, the similarity between the entrepreneur and the role model, and the strength of their relationship.
Keywords: L26; M13; J24; 330; role models; entrepreneurs; human capital; new firm start-ups; Unternehmer; Soziale Rolle; Unternehmensgründung; Humankapital; Selbstständige; Niederlande